Mitochondrial circular RNAs are absent in sporulating cells of Saccharomyces cerevisiae. - Schroeder, R (1983)
During sporulation of Saccharomyces cerevisiae the mitochondria undergo a differentiation process, leading to a "spore mitochondrion", which differs both physiologically and morphologically from vegetative cell mitochondria. We report here the behaviour of the mitochondrial transcripts during this differentiation process. The circular transcripts representing spliced introns of the two mitochondrial split genes for cytochrome b and for the subunit 1 of the cytochrome c oxidase, which are very abundant during vegetative growth, are not detectable in sporulating cells. This loss does neither take place in haploid cells under sporulation conditions nor when erythromycin is added to the medium. The process of some mRNAs is advanced in relation to their precursors in sporulating cells.